(untitled) (Journal of Medical Device Technology, 2022)
Edible bird’s nest (EBN) derived from saliva of swiftlet is often consumed for its nutritional benefit. In this study, EBN natural soap was studied based on their morphology, antibacterial activity and cytotoxicity. The surface morphology and the presence of heavy metal in the soaps were investigated through scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDX). The antibacterial activity of EBN natural soap against Escherichia coli ATCC 25922 was investigated using disc diffusion and bacterial colony count method while the biocompatibility property was determined with human skin fibroblast cells through MTT assay and morphology observation under an inverted microscope. A consistent surface morphology pattern and no heavy metal were recorded on the soaps. The results of antibacterial activity indicated that the EBN natural soap did not have any antibacterial property but able to retain high cell viability percentage of 91.88±3.04% with normal cell morphology. Therefore, the EBN natural soap is biocompatible and appropriate to be incorporated in skin products.